High Branched‐Chain Amino Acid Concentrations Are Found in Preterm Baboons Receiving Intravenous Amino Acid Solutions and Mimic Alterations Found in Preterm Infants. Issue 8 (7th February 2019) - Blanco, Cynthia; McGill‐Vargas, Lisa; Li, Cun; Winter, Lauryn; Nathanielsz, Peter
Abstract: Background: Parenteral amino acid (AA) nutrition administration after premature birth is necessary to ensure adequate growth and neurodevelopment. However, optimizing safety and efficacy remains a major challenge. This study investigated the effects of intravenous AA administration on plasma AA profiles in premature baboons and infants. Methods: Premature baboons were delivered by cesarean section at 125 days (67% gestation) and chronically ventilated. At 24 hours of life, a parenteral AA protocol comparable to the early and high AA regimens used in premature infants was initiated. Serial plasma AA concentrations were obtained on days of life (DOLs) 1, 3, and 7 and compared with concentrations at similar DOLs from preterm infants. Fetal baboon (165 ± 2 days; 89% gestation) and term baboon plasma AA concentrations were obtained for comparison. Results: Premature baboons receiving early and high parenteral AA supplementation exhibited significant differences in plasma AA concentrations compared with fetuses. In particular, concentrations of leucine, isoleucine, valine, and ornithine were elevated (fold increase: 2.14, 2.03, 1.95, and 16.5, respectively; P < 0.001) on DOL 3 vs fetuses. These alterations mimicked those found in preterm infants. Conclusion: Early and high AA supplementation in extremely premature baboons significantly disrupted plasma AA concentrations. Elevated concentrations of branched‐chain AAs and ornithine raise concerns for adverse neurodevelopmental outcomes. These results are consistent with those found in premature human infants and emphasize the need to optimize parenteral AA solutions for the unique metabolic requirements of premature infants. Improved technologies for rapid monitoring of AA concentrations during treatment are essential.